Edited Platforms: Anticipating Future Consumption. Issue 2 (2nd April 2016) - Adams, Russell; Downey, Clara
Abstract : The modern world is witnessing many technological, demographic, and consumption changes. The purpose of this conceptual article is to combine these shifts into a model that will assist companies to improve plans for the future marketplace. The authors present a new concept, "edited platforms, " as a consumer aware, but company driven, product development model. Examples of the concept are explicated, and projected implications are provided. Propositions for further study are provided, along with suggestions for marketing and theoretical implications.